The accountant 2 [videorecording (DVD)] - Dubuque, Bill; Affleck, Ben, 1972-; Bernthal, Jon; Addai-Robinson, Cynthia, 1985-; Pineda, Daniella, 1987-; Robertson, Allison; Morgan, Robert (Actor); Simmons, J. K.; McGarvey, Seamus, 1967-; Dessner, Bryce; Mussenden, Isis, 1959- (Amazon MGM Studios, 2025)
Christian Wolff has a talent for solving complex problems. When an old acquaintance is murdered, leaving behind a cryptic message to 'find the accountant,' Wolff is compelled to solve the case. Realizing more extreme measures are necessary, Wolff recruits his estranged and highly lethal brother, Brax, to help. In partnership with U.S. Treasury Deputy Director Marybeth Medina, they uncover a deadly conspiracy, becoming targets of a ruthless network of killers who will stop at nothing to keep their secrets buried.